Corrections to “Combining Convolutional Neural Networks for Fungi Classification” - Anuruk Prommakhot; Jakkree Srinonchat (IEEE Access)
Presents corrections to the paper, Corrections to “Combining Convolutional Neural Networks for Fungi Classification”.